Analysis of mesoscale modelling strategies for woven composites. Issue 3 (4th February 2020) - Ma, Dayou; Giglio, Marco; Manes, Andrea
Abstract: Considering the wide applications of composite material, it is crucial to understand the corresponding damage mechanisms and mechanical response during the loading process. To achieve this aim, a mesoscale modelling strategy has been employed to provide these details. The voxel mesh and volume mesh are two types of commonly‐used mesh morphologies to build a mesoscale Finite Element (FE) model. However, during the establishment of a FE mesoscale model, the effect of unit cell section, mesh size and mesh morphology on the simulation results is rarely analysed in a comprehensive way. In the present work, FE models with various mesh morphologies, unit cells and mesh sizes were built for a glass‐fibre woven composite. Parametric analysis was performed under tensile and shear loading conditions and the simulation results were compared based on test data. Further, guidance about the selection of the mesh morphology, unit cell and mesh size were provided for the establishment of a mesoscale model of woven composites.